A new method for the measurement and analysis of biomechanical energy delivered by kicking - Ramakrishnan, K. R.; Wang, H.; Shankar, K.; Fien, A. (Sports Engineering, 2018)
An accurate measurement of force and biomechanical energy that people can impart through kicking is useful for kick-related sports training. Existing methods are indirect measurements or focus on force and not on the total energy of the kick. A kick test rig was designed, constructed and instrumented to measure the force and displacement of a vertical target subjected to kicking. The kick energy was calculated from the recorded force and displacement histories. The methodology for measurement of kick force and energy was validated by an open stance front kick test by 52 volunteers. The results showed that 67% of the participants could achieve an average energy above 100 J. An increasing trend of kick energy with increasing body weight of participant was observed. The participant`s gender had a strong influence on the kick energy, while training in martial arts does not appear to be a significant parameter. A probability analysis showed that one in one hundred adults will be able to kick with energies exceeding 215 J.